Reversible Iron Oxyfluoride (FeOF)‐Graphene Composites as Sustainable Cathodes for High Energy Density Lithium Batteries. Issue 15 (11th January 2023) - Liu, Yadong; Yu, Yikang; Yang, Fan; Zhu, Guangqi; Yu, Kang; Kou, Ronghui; Sun, Chengjun; Liu, Yuzi; Xu, Jiayi; Liu, Cong; Li, Chenzhao; Liu, Tianwei; et al.
Abstract: Two large barriers are impeding the wide implementation of electric vehicles, namely driving‐range and cost, primarily due to the low specific energy and high cost of mono‐valence cathodes used in lithium‐ion batteries. Iron is the ideal element for cathode materials considering its abundance, low cost and toxicity. However, the poor reversibility of (de)lithiation and low electronic conductivity prevent iron‐based high specific energy multi‐valence conversion cathodes from practical applications. In this work, a sustainable FeOF nanocomposite is developed with extraordinary performance. The specific capacity and energy reach 621 mAh g −1 and 1124 Wh kg −1 with more than 100 cycles, which triples the specific capacity, and doubles the specific energy of current mono‐valence intercalation LiCoO2 . This is the result of an effective approach, combing the nanostructured FeOF with graphene, realized by making the (de)lithiation reversible by immobilizing FeOF nanoparticles and the discharge products over the graphene surface and providing the interparticle electric conduction. Importantly, it demonstrates that introducing small amount of graphene can create new materials with desired properties, opening a new avenue for altering the (de)lithiation process. Such extraordinary performance represents a significant breakthrough in developing sustainable conversion materials, eventually overcoming the driving range and cost barriers. Abstract : A sustainable graphene‐incorporated iron oxyfluoride nanocomposite is developed for high energy density lithium batteries. The FeOF‐G allows for a 2.1‐vanlence change for reversible lithium storage, leading to a high specific capacity and energy of 621 mAh g −1 and 1124 Wh kg −1, respectively. Such extraordinary performance represents a significant breakthrough in developing sustainable conversion battery materials for replacing intercalation compounds.